MODERNISME DAN REFORMISME DALAM PEMBINAAN HUKUM ISLAM DAN PRANATA SOSIAL - Bahdar, Bahdar (State Institute of Islamic Studies (IAIN) Palu, 2013)
Abstract. This paper describes the development of modernism and reformism in Islamic law and social institutions. This study is directed to the existence of Islamic law in the midst of social change. Islamic law is eternal is faced with an ever-changing social reality, has attracted serious attention in many scientific experts. It is a debate among scholars orientalis is about environmental adaptability of Islamic law with the social development of society. Society always change with the change of time and place, while sharia law final and eternal nature. In connection with the issue, it is questionable whether Islamic law can be developed and can accommodate the interests of humanity that is always moving forward. Or whether only follow God set eternity.Kata kunci: modernisme, reformisme, hukum Islam, pranata sosial